Selection of marine fish for integrated multi-trophic aquaponic production in the Mediterranean area using DEXi multi-criteria analysis - Rossi, Lorenzo; Bibbiani, Carlo; Fierro-Sañudo, Juan Francisco; Maibam, Chingoileima; Incrocci, Luca; Pardossi, Alberto; Fronte, Baldassare (Aquaculture, 2021)
Producing food according to the sustainability and “circular economy” principles is considered a strategic goal by several world Institutions. Integrated Multi-Trophic Aquaculture (IMTA) responds to these criteria and stemming from it, the “Self-sufficient Integrated Multitrophic AquaPonic” (SIMTAP) aims to drastically reduce production inputs and waste outputs while maximizing the total food production. In order to succeed, proper selection of the most suitable fish, intermediate organisms and plant species to be grown in the system plays a fundamental role. To validate the SIMTAP concept and experimental prototype, the biological characteristics of fish and other species should be assessed taking into account their complementarity and adaptability to the physical and technical traits of the considered system. This study aimed to identify the most suitable marine organisms for food production within the SIMTAP system and to create a decision model via the DEXi decision support system. Hence, in the present work a brief description of the SIMTAP concept, as well as the biological, zootechnical and commercial characteristics of several candidate fish species, are discussed. The criteria considered to address the species selection were: natural geo-distribution, domestication degree, environmental requirements, feeding regime, growth performances, and market value. The candidate species were: Sparus aurata, Dicentrarchus labrax, Mugil cephalus, Diplodus puntazzo, Seriola dumerili, Umbrina cirrosa, Argyrosomus regius, Psetta maxima, Acipenser spp., Solea spp., Octopus vulgaris. Finally, it seems that the DEXi approach increased the objectivity of the species selection process. Gilthead Sea Bream, European Sea Bass and Flathead Grey Mullet resulted to be the most suitable species for SIMTAP production. •Selecting suitable fish species for marine/brackish water land based IMTA systems•Literature review of the most common aquaculture species in the Mediterranean area•Multi-criteria decision method (DEXi) to select the suitable species•The suitable species selected by DEXi are Sparus aurata and Dicentrarchus labrax•DEXi represents a comprehensive tool for species selection in aquaculture and IMTA